Photoselective shade Nets in agriculture (Research, Society and Development, 2020)
Use of photoselective networks started in the 90s and are used as barriers that filter solar energy. Plants have different physiological and morphological responses based on the photoselective network. The purpose of this bibliographic review is to analyze the main researches on the use of photoselective networks in agriculture. The work consists of an integrative literature review based on original articles in the English language from the Elsevier, Google Scholar, Scielo, Science Direct, Taylor & Francis and Web of Science databases. Of the 29 articles selected for a survey, only 17 were used (58.62%). He observed that in the 17 articles used, the use of photoselective nets was advantageous in agriculture. The literature makes it clear that photoselective networks are widely used in agriculture - in the areas of horticulture, fruit and ornamental plants - with the aim of reducing climate change and increasing its morphological or physiological characteristics.